53.5k views
4 votes
How do you find the same y intercept

How do you find the same y intercept-example-1

2 Answers

4 votes

Answer: Choice C

f(x) - 1 and g(x) + 1

=============================================

Step-by-step explanation:

Plug x = 0 into f(x)

f(x) = 4x + 1

f(0) = 4(0) + 1

f(0) = 1

The y intercept of f(x) is 1

----------

Now plug x = 0 into g(x)

g(x) = 3^x - 2

g(0) = 3^0 - 2

g(0) = -1

The y intercept of g(x) is -1

----------

Note how the y intercepts are 2 units apart.

Each of the answer choices are in the form of f(x) + M and g(x) + N. The goal is to see which M and N values will be 2 units apart. In this case, that would be choice C where M = -1 and N = 1

We see that f(x) - 1 = f(0) - 1 = 1 - 1 = 0 and g(x) + 1 = g(0) + 1 = -1 + 1 = 0

Therefore, f(x) - 1 and g(x) + 1 have the same y intercept of 0.

User Dabluck
by
4.5k points
2 votes

Answer:

D

Step-by-step explanation:

The y-intercept is the number or constant at the end of the equation.

D sets both of their y-intercepts to -6, so it's correct.

User Vishnu Satheesh
by
5.7k points